Depression and the Risk of Peptic Ulcer Disease: A Nationwide Population-Based Study. Issue 51 (December 2015) - Hsu, Chih-Chao; Hsu, Yi-Chao; Chang, Kuang-Hsi; Lee, Chang-Yin; Chong, Lee-Won; Lin, Cheng-Li; Shang, Chuin-Shee; Sung, Fung-Chang; Kao, Chia-Hung
Abstract : Abstract: The risk of peptic ulcer disease (PUD) among patients with depression has raised concern. This study determined the association between depression and the subsequent development of PUD using claims data. Patients newly diagnosed with depression in 2000 to 2010 were identified as depression cohort from the Taiwan National Health Insurance Research Database. The comparison cohort was randomly selected from subjects without depression, frequency matched by age and gender and diagnosis date, with a size 2-fold of the size of the depression cohort. The incidence of PUD was evaluated for both cohorts by the end of 2011. We calculated the hazard ratios (HRs) and 95% confidence intervals (CIs) of PUD using the Cox proportional hazards regression model. The depression cohort consisted of 23, 536 subjects (129, 751 person-years), and the comparison cohort consisted of 47, 069 subjects (285, 592 person-years). The incidence of PUD was 2-fold higher in the depression cohort than in the comparison cohort (33.2 vs 16.8 per 1000 person-years) with an age adjusted HR of 1.97 (95% CI = 1.89–2.06) or a multivariable adjusted HR of 1.35 (95% CI = 1.29–1.42). Depression might increase the risk of developing PUD. Prospective clinical studies of the relationship between depression and PUD are warranted.